Operational stability of immobilised lipase/acyltransferase during interesterification of fat blends - Osório, Natália Melo (2009)
The lipase/acyltransferase from Candida parapsilosis is an unusual enzyme that preferably catalyses alcoholysis over hydrolysis in biphasic aqueous/organic media. The aim of this study was to evaluate the operational stability of an immobilised form of this enzyme during the interesterification of fat blends containing n-3 polyunsaturated fatty acids, in solvent-free media, at 60 7C, carried out continuously and batchwise. When the interesterification was performed in a continuous fluidised-bed reactor, an operational half-life of 9 h was estimated. The biocatalyst was also reused in consecutive 23-h batches, in a total of four batches, either using fresh medium with no water addition or adding water to rehydrate the biocatalyst. When no water and extra water was added to the reaction medium, the obtained half-lives were 10 and 18 h, respectively. Thus, the loss of activity may be explained by a progressive dehydration occurring along the reaction rather than by product or substrate inhibition effects. The interesterification activity was accompanied by changes in the acylglycerol profile. An increase in compounds of low equivalent carbon number (ECN) and in triacylglycerols (TAG) of ECN 42 and 44 was observed. This increase was accompanied by the consumption of TAG of ECN 46, 48 and 50